Daily activity patterns and thermal tolerance of three sympatric dung beetle species (Scarabaeidae: Scarabaeinae: Eucraniini) from the Monte Desert, Argentina - Gimenez Gomez, Victoria Carolina (2017)
Tolerance to extreme temperatures, thermal limits, and the mechanisms of thermoregulation are related to internal functions of insects and partly define their ecological niche. We study the association between daily activity of dung beetles from the Monte Desert in Argentina and their tolerance to high temperatures. Results indicate that for all three sympatric species studied, Eucranium belenae Ocampo, Anomiopsoides cavifrons (Burmeister), and Anomiopsoides fedemariai Ocampo, daily activity is associated to ground temperature. Eucranium belenae is active when ground temperature is relatively low and it is less tolerant to long periods of activity at high temperatures in the lab, while A. cavifrons and A. fedemariai are active when ground temperatures are higher, and they tolerate high temperatures for longer periods of time than E. belenae in the lab. These species coexist and use similar food sources, and this eco-physiological study may help to explain how they differentiate under the same environmental conditions. The Monte Desert is considered an extreme environment, and studies on thermal tolerance offer testable predictions to understand how species would respond to climate change.